Middle‐aged to elderly women have a higher asymptomatic infection rate with Mycobacterium avium complex, regardless of body habitus. Issue 3 (7th December 2015) - Nishimura, Tomoyasu; Fujita‐Suzuki, Yukiko; Mori, Masaaki; Carpenter, Stephen M.; Fujiwara, Hiroshi; Uwamino, Yoshifumi; Tamizu, Eiko; Yano, Ikuya; Kawabe, Hiroshi; Hasegawa, Naoki
Abstract : M ycobacterium avium complex (MAC) pulmonary disease is prevalent in middle‐aged to elderly women with a thin body habitus. By comparing the rate of serologically diagnosed asymptomatic MAC infection and body mass index among 1033 healthy subjects, we find that middle‐aged to elderly women became infected with MAC, regardless of their body habitus.